Subjective quality of life in psychosis: Evidence for an association with real world functioning?. (March 2018) - Leendertse, Pien; Myin-Germeys, Inez; Lataster, Tineke; Simons, Claudia J.P.; Oorschot, Margreet; Lardinois, Mariëlle; Schneider, Maude; van Os, Jim; Reininghaus, Ulrich; ,
Abstract: Subjective quality of life (SQOL) is an established patient-reported outcome in psychosis. However, current self-report measures of SQOL may be affected by recall bias and may not fully capture dynamic changes in SQOL over time. This study aimed to examine the ecological validity of self-reported and momentary assessment measures of SQOL, and their association with emotional experience, social interaction and activity in real life, in both patients with psychotic disorder (n = 56) and controls (n = 71). Self-reported QOL was assessed with the WHO-QOL, momentary QOL and real life experiences were assessed with the Experience Sampling Method (ESM). Results show that both measures were significantly associated in patients and controls, and associations with emotional experience were most relevant, momentary QOL being a stronger predictor than self-reported QOL. The association between momentary QOL and negative affect was stronger in patients than in controls. Overall, momentary QOL was more consistently associated with affect, social interaction and activity, while self-reported QOL displayed a more narrow association with mostly affect. Concluding, concurrent assessment of self-reported QOL and momentary QOL showed that momentary QOL may enhance the ecological validity of SQOL measurement. Experience sampling research may broaden our perspective on SQOL and its associations with real life functioning. Highlights: The association between subjective QOL and real life experiences is strongest for affect. The association between momentary QOL and negative affect is stronger in patients. Momentary QOL is more consistently associated with real life experiences than self-reported QOL.